PSYCHOPREVENTIVE PRINCIPAL APPROACHES TO PREVENTING INFORMATION THREATS AMONG YOUTH - Hayitova H.M. (International Journal of Business, Law and Political Science, 2024)
The rapid expansion of digital information has heightened the vulnerability of young people to various information threats, necessitating effective prevention strategies. General Background: In an increasingly connected world, the psychological resilience of youth is critical for safeguarding against the adverse effects of information overload and addictive behaviors. Specific Background: This article explores psychoprophylactic approaches aimed at enhancing psychological stability and mitigating negative impacts, focusing on comprehensive strategies that address the multifaceted nature of these threats. Knowledge Gap: Despite existing literature, there remains a lack of cohesive frameworks that integrate medical, educational, and psychosocial models for the prevention of addictive behavior among young individuals. Aims: This study aims to analyze current strategies and measures designed to fortify the psychological defenses of youth and to propose effective prevention frameworks. Results: The findings reveal a range of successful interventions, including programs that enhance social and personal competencies, as well as various prevention approaches that have shown promise in clinical and educational settings. Novelty: This research contributes to the existing body of knowledge by synthesizing diverse models and identifying best practices in the field of information threat prevention. Implications: The insights derived from this analysis can inform policymakers, educators, and mental health professionals in developing targeted initiatives that not only protect young individuals from information-related risks but also promote their overall psychological well-being.